The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/la900087c
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Papain and Neuraminidase Enzyme Treatment on Electrohydrodynamics and IgG-Mediated Agglutination of Type A Red Blood Cells

Abstract: The stability of native and enzyme-treated human red blood cells of type A (Rh D positive) against agglutination is investigated under conditions where it is mediated by immunoglobuline G (IgG) anti-D antibody binding. The propensity of cells to agglutinate is related to their interphasic (electrokinetic) properties. These properties significantly depend on the concentration of proteolytic papain enzyme and protease-free neuraminidase enzyme that the cells are exposed to. The analysis is based on the interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 60 publications
(120 reference statements)
1
26
0
Order By: Relevance
“…(1)-(7) disregard (i) polarization of electric double layer by the applied field and (ii) the possible heterogeneity in soft material density distribution within the permeable part of the bacteria, heterogeneity occasioned by possible swelling of the soft bacterial component under low ionic-strength conditions. As extensively demonstrated in previous work [33,36,37], phenomena (i) and (ii) effectively lead to reduced mobility (in magnitude) as compared to those obtained from Eqs. (1)- (7).…”
Section: Volume Charge Density ( 0 ) and Softness Parameter ( 0 ) Of supporting
confidence: 65%
See 1 more Smart Citation
“…(1)-(7) disregard (i) polarization of electric double layer by the applied field and (ii) the possible heterogeneity in soft material density distribution within the permeable part of the bacteria, heterogeneity occasioned by possible swelling of the soft bacterial component under low ionic-strength conditions. As extensively demonstrated in previous work [33,36,37], phenomena (i) and (ii) effectively lead to reduced mobility (in magnitude) as compared to those obtained from Eqs. (1)- (7).…”
Section: Volume Charge Density ( 0 ) and Softness Parameter ( 0 ) Of supporting
confidence: 65%
“…For the sake of illustration, recent analysis demonstrated that electrokinetics is a fast and valuable tool for detecting surface structure modifications/alterations undergone by soft bioparticles like blood cells or yeasts as a result of the action of biospecific molecules like e.g. enzymes [37,38]. In the current study, electrophoretic mobilities measured as a function of KNO 3 solution ionic strength were quantitatively interpreted on the basis of the analytical theory developed by Ohshima which accounts for the electrokinetic response of soft cylindrical particles [39].…”
Section: Evaluation Of Electrohydrodynamic Properties Of L Pneumophimentioning
confidence: 99%
“…The diffuse character of the polyelectrolyte layer is defined by a gradual distribution of the density of polymer segments in the interspatial region separating the core from the bulk electrolyte solution. Successful application of that model has been reported for humic acids [46], bacteria [47] and red blood cells [48]. For numerical calculations of the electrophoretic mobility based on more rigorous theories, the readers are referred to the studies of Hill et al [49][50][51][52] and Lopez-Garcia et al [53][54][55] as well as that of Duval and Ohshima [45].…”
Section: Electrophoretic Mobility Of Soft Particlesmentioning
confidence: 99%
“…This means that the mean field approximation fails on the periphery of diffuse polyelectrolyte layers where the density of charged segments is lower than a given critical value. Despite this difficulty and the underlying limitations of the model, failure of the mean-field approach for electrostatics in the very diffuse portion of the gel layer is not fatal because previous experimental and theoretical publications on numerous (bio)colloidal systems [58][59][60] demonstrated that the electrokinetics of soft diffuse interfaces is for a large part dominated by the hydrodynamics and not by the electrostatics of the tails of charged segments pointing toward the solution. Rigorously, this means, that a correction term should be added to the governing electrostatic equation and that the impact of this term on the overall electrokinetic response of the system should turn out to be small and thus could be possibly disregarded.…”
Section: The Brinkman Equation and Electrokinetics Of Diffuse Soft Sumentioning
confidence: 99%